Nitrous oxide emissions from a typical argiudol soil with organic and chemical amendments = Emisiones de óxido nitroso desde un suelo argiudol típico con enmiendas orgánicas y químicas - Cosentino, Vanina Rosa Noemi; Pérez, Mónica Gabriela; Ostinelli, Mauro Ezequiel; Romaniuk, Romina Ingrid; Mortola, Natalia Andrea; Rizzo, Pedro Federico; Costantini, Alejandro Oscar (Asociación Argentina de la Ciencia del Suelo, 2022)
Diversification in fertilizer sources will be necessary to meet the growing demand for food worldwide. For this reason, organic amendments emerge as a synthetic fertilizers alternative. Composting organic waste stabilizes the nitrogen (N) content and delays N release to the soil. Applying composted amendments to the soil could reduce the losses of N, including nitrous oxide (N2O), a greenhouse gas with great potential for global warming. The objective of this work was to evaluate the N2O emission in typical Argiudol soil after applying a traditional synthetic fertilizer, raw poultry manure, composted poultry manure and control soil. Cumulative N2O emission rates during the 32 days of the trial were 1273, 965, 423, and 244 g N2O-N/ha-1 from the soil using urea, poultry manure, composted poultry manure, and control, respectively. Our results suggest that the application of composted poultry manure to the soil produces lower N2O emissions than the application of raw poultry manure or urea. The presence of more stabilized compounds in the composted manure decreases the soil nitrate availability.